Literasi Matematika Siswa dalam Menyelesaikan Soal Model PISA Ditinjau dari Gaya Kognitif Sistematis-Intuitif - Hanum Kholidah Ziya; Susanah Susanah (Universitas Negeri Surabaya, 2026)
Mathematical literacy is an individual's ability to formulate, employ, and interpret mathematical concepts and procedures to solve contextual problems. This study aims to describe students’ mathematical literacy with systematic and intuitive cognitive styles in solving PISA model problems. This study used a descriptive qualitative approach involving two ninth-grade students with different cognitive styles, the same gender, and equivalent high mathematical abilities. Data were collected through PISA model problems and semi-structured task-based interviews, then analyzed through data reduction, data presentation, and conclusion drawing based on PISA mathematical literacy indicators. The results showed that both students fulfilled the three mathematical literacy processes with different characteristics. In the formulate process, systematic students tended to understand problems thoroughly and construct complete mathematical representations, while intuitive students focused on contextual visualization and identifying important information. In the employ process, systematic students used structured solution steps, whereas intuitive students applied practical strategies and intuition. In the interpret process, systematic students evaluated results analytically based on contextual suitability, while intuitive students emphasized practical and visual interpretation. Therefore, cognitive style influences students’ approaches in solving PISA model problems.